Does extra feed after breeding affect litter size? - Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1991)
Fertility was evaluated in sows fed 4 vs 10 lb/d and gilts fed 4 vs 7.4 Ibid during the first 10 days after breeding. No effects on farrowing rate or litter traits were detected. This confirms results of a previous KSU experiment. Therefore, high feed intake after breeding may not affect fertility traits.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Sows; Intake; Reproductive performance; Gestation